A grooved in-plane torsion test for the investigation of shear fracture in sheet materials. (1st August 2015) - Yin, Q.; Soyarslan, C.; Isik, K.; Tekkaya, A.E.
Abstract: The grooved in-plane torsion test is proposed as a shear fracture test for sheet materials. Unlike conventional simple shear tests, which are prone to incipient cracking at the free edges, this test uses radially continuous specimens, as firstly introduced by Marciniak and Kołodziejski (1972). In order to control the fracture position, a radial groove is cut out which allows to keep the fracture away from the clamping area. Thus, this test is able to create material fracture under ideal shear conditions i.e., the condition of vanishing triaxiality at the observable region of the test. Accordingly, the recent shear extended damage and fracture models for the selected material classes can be validated and/or quantified. With the help of finite element analysis (FEA), the corresponding fracture strains for the steel DP1000 were investigated using the proposed shear test and, additionally, three tensile tests conducted on notched specimens which cause fracture at moderate to high triaxialities. These are used to fit the fracture loci of some shear enhanced fracture criteria which have recently been proposed in the literature. The FEA shows that the proposed test provides fracture development under constantly zero triaxiality and zero Lode parameter conditions. Moreover, among the selected criteria, the model proposed by Lou et al. (2012) delivers the best results for selected experimental set. The developed test is ideally suitable for fracture parameter identification of sheet materials which do not show pronounced in-plane anisotropy, e.g. dual phase steels. Furthermore, this test is not limited to metallic materials.